THE « EMPEROR» OF GERMAN GYNECOLOGISTS AND OBSTETRICIANS - J. W. Dudenhausen (Акушерство, гинекология и репродукция)
The article highlights the main stages of life and work of the outstanding specialist in female diseases – German obstetrician, gynecologist, surgeon, scientist Walter Stoeckel.